Demand for Imports and Components of Final Expenditure: An Empirical Study with Special Reference to the Korean Import Demand Function - Yoon, Il-Hyun; Seddighi, H. R. (Asian Journal of Economics and Empirical Research, 2019)
This paper presents a detailed empirical investigation of Korea’s demand for imports. In particular, our study provides fresh estimates of partial elasticities of demand for imports with respect to each key component of final expenditure including final consumption expenditure, and expenditure on capital formation. A Johansen multivariate co-integration analysis is employed on the post-global financial crisis quarterly macroeconomic data such as final consumption, gross fixed capital formation, exports and relative import prices for the sample period 2009-2018. In support of the empirical framework used in this study, we have found significant differences to exist between various long-run partial elasticities of demand for imports while import elasticity of demand with respect to expenditure on fixed capital formation is found to be negative. This latter result appears to imply that incremental increases in capital formation can provide an effective mechanism for reducing reliance of Korea on imports in the long run. According to the short-run forecasting model, we have found that the current period changes in the demand for imports are related only to the previous period changes in relative price of imports.